Of Mice and Men Opera Still - Ron Scherl:::Creator::::::::::::
The Spring Opera Theater production of Carlisle Floyd's "Of Mice and Men' opera adaptation. Alexandra Hunt (Curley's Wife) standing in a dress, facing the camera with William Neill (Lennie) in the background, lying on his back in a hayloft.